Desafios para a formação de parcerias no serviço creche da Secretaria da Assistência Social da PMSP - Ramos, Ana Marcia Fornaziero (2003)
We investigated the bonds established by means of contracts between governmental sector and the nonprofits sector to provide public’s services to the community in special in the child area. This study analyzed the agreement that have been done between the Secretaria de Assistência Social (SAS) (Secretariat of Social Assistance) of PMSP (City Hall of São Paulo) and Nonprofit Organizations in the provision of crèches service. We defined partnerships as being substantive relations that imply responsibility from both sides, sharing of values and compromise from each other. To reaching this definition we did literature revision in this field, documentary research and study of cases interviewing everybody that work together when an agreement is done. We analyzed four private crèches which receive subsidy from government (and their respective Nonprofit Organizations), two crèches that are administered directly by the government and Regional SAS from Itaquera Guaianazes and Central SAS. We chose crèches that got a good evaluation by their results. We showed that the services provided directly by government are so important as the service provided by Nonprofit Organization. Both can have good quality and both need to have transparency in their actions, constant dialogues, understanding of their roles and they should be accountable. The provision of social service by means of Nonprofit Organization is justified because nowadays they have an important role in the lives of the citizens and because all society should have responsibility concerning social problems. The provision of social service by government is justified because we consider that State is the most important player which has to take in his own hand the responsibility of guaranteeing welfare state for every citizen. This study indicated as a challenge the necessity to review the form how the bonds are being done between the studied agents in purpose of establishing partnerships, as well as the challenge of the government taking in his hands the conduction of public politics in the social field including in it the actions of the Nonprofit Organizations.